Myvolunteermapper: an online volunteer mapping system for helping vulnerable communities in Malaysia / Sakinah Anisah Khairul Anuar and Abdul Rauf Abdul Rasam - Khairul Anuar, Sakinah Anisah; Abdul Rasam, Abdul Rauf (Universiti Teknologi MARA, Perak, 2020)
Many people all over Malaysia are affected by natural disasters and disease outbreaks. Humanitarian aid workers are needed for serving these communities. The locations of the most susceptible communities and information of volunteers are also worthy for urgent assistance and humanitarian aid response. Unfortunately, the absence of a complete geospatial system and data of volunteers especially when there are events that require the data immediately are main concerns in this research. Therefore, a geoinnovation system of MyVolunteerMapper was developed creatively. This web-based multimedia mapping system is used as a decision tool in making and sharing geo-information on the volunteers in Malaysia. The features of this system are mapping of position of volunteers and proposed events, extraction of data by query, distance measurement, searching for volunteers on specific distance by buffering, time travelling using network analysis and business analyst for local demographic. Therefore, this system could be applied to find the most suitable volunteers in the specific location for humanitarian programmes.